Dinâmicas de complexificação e simplificação do trabalho em meio ao processo de reestruturação produtiva no Brasil: possíveis impactos na formação/educação profissional - Bello de Souza, Donaldo (Boletim Técnico do Senac, 2002)
This article examines aspects that are helping to achieve the demarcation and portrayal of the Brazilian production restructuring process, based on the search of a possible differentiation existing in connection with the adoption of innovations by industrial plants most exposed to the international market requirements and those largely committed to the domestic market. Generally speaking, it is possible to say that the productive restructuring process in both focused sectors is singled out more for its massive adoption of organizational than technological innovations, witnessed in a larger degree and intensity at the sector sending its products out to the international markets. While the technological innovations would be causing the work to be simplified in a larger scale, those of an organizational nature would be causing it to grow into a more complex structure.